Calcium interactions in amelogenin-derived peptide assembly - Zhang, Jing; Bai, Yushi; Wang, Jian; Li, Bing; Habelitz, Stefan; Lu, Jun-xia (Frontiers in Physiology, 2022)
Phosphorylation of serine residues has been recognized as a pivotal event in the evolution of mineralized tissues in many biological systems. During enamel development, the extracellular protein matrix, protein supra-assemblies with amelogenin most abundantly, appears to be critical to the extreme high aspect ratios (length:width) of apatite mineral fibers reaching several millimeters in larger mammalian teeth. A 14-residue peptide (14P2) was previously identified as the key sequence mediating amelogenin assembly formation, which also contains the native single phosphoserine residue (Ser16) of the full-length amelogenin. In this research, 14P2 and its phosphorylated form (p14P2) were investigated at pH 6.0 with various calcium and phosphate ion concentrations, indicating that both peptides could self-assemble into amyloid-like conformation but with differences in structural details. With calcium, the distance between 31P within the p14P2 self-assemblies is averaged to be 4.4±0.2Å, determined by solid-state NMR 31P PITHIRDS-CT experiments. Combing with other experimental results, SSNMR indicates that the p14P2 self-assemblies are in parallel in-register β-sheet conformation and the calcium binding sites include the phosphate group on Ser16 and the carboxylate of Glu18 side-chain.The study of the interactions between calcium ions and the amelogenin-derived peptides would give insights on how amelogenin interacts with calcium ions in the native state.